2019
DOI: 10.1136/medethics-2019-105675
|View full text |Cite
|
Sign up to set email alerts
|

Should pregnant women be charged for non-invasive prenatal screening? Implications for reproductive autonomy and equal access

Abstract: The introduction of non-invasive prenatal testing (NIPT) in healthcare systems around the world offers an opportunity to reconsider funding policies for prenatal screening. In some countries with universal access healthcare systems, pregnant women and their partners are asked to (co)pay for NIPT. In this paper, we discuss two important rationales for charging women for NIPT: (1) to prevent increased uptake of NIPT and (2) to promote informed choice. First, given the aim of prenatal screening (reproductive auto… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
31
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 23 publications
(32 citation statements)
references
References 44 publications
(58 reference statements)
1
31
0
Order By: Relevance
“…The comparison of our findings in Lebanon and in Quebec points out the reasons underlying a similar concern raised by the routinization of NIPT: the potential increase in pregnancy terminations, which has been as well reported in other studies [36,37]. Since prenatal testing is inevitably linked to the abortion debate -as it may lead couples and pregnant women to consider whether to continue or terminate a pregnancy, abortion policy in place is of utmost relevance.…”
Section: Discussionsupporting
confidence: 78%
“…The comparison of our findings in Lebanon and in Quebec points out the reasons underlying a similar concern raised by the routinization of NIPT: the potential increase in pregnancy terminations, which has been as well reported in other studies [36,37]. Since prenatal testing is inevitably linked to the abortion debate -as it may lead couples and pregnant women to consider whether to continue or terminate a pregnancy, abortion policy in place is of utmost relevance.…”
Section: Discussionsupporting
confidence: 78%
“…Third, public funding may help to improve informed decision making and restore correct understandings of the target group of first-trimester screening programmes in countries like the Netherlands, with universal coverage healthcare systems. As we have argued, funding policies are not neutral: 1 by offering NIPT free of charge, the state may be seen to support or endorse screening, and, vice versa, by requesting a (co)payment, the state may be seen to discourage screening or deem it unimportant. The latter is of particular concern in our country.…”
mentioning
confidence: 97%
“…In a recent paper in Journal of Medical Ethics , we have shown that policies requiring pregnant women to (co)pay for non-invasive prenatal testing (NIPT) raise financial barriers that will not improve informed decision making. 1 Also, they may exacerbate problems regarding equity of access to prenatal screening by disproportionally affecting women of lower socioeconomic status. 1 In a response, Dagmar Schmitz rightfully points out that the paper does not, however, provide a justification for public funding of NIPT tout court.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Bunnik and colleagues made an important contribution to a highly topical debate concerning ethical aspects of funding policies for prenatal screening 1. However, their case for public funding of non-invasive prenatal testing (NIPT) is not completely convincing.…”
mentioning
confidence: 99%